2008
DOI: 10.1002/ijc.24031
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anti‐tumor effect of paclitaxel with CRM197, an inhibitor of HB‐EGF, in ovarian cancer

Abstract: Heparin-binding EGF-like growth factor (HB-EGF) plays a pivotal role in tumor growth and clinical outcomes in patients with ovarian cancer, leading to the validation of HB-EGF as a target for ovarian cancer therapy. In this study, we investigated the antitumor effects of paclitaxel, as an anti-cancer agent, and CRM197, as a specific inhibitor off HB-EGF, in ovarian cancer. Paclitaxel induced transient ERK activation and sustained activation of JNK and p38 MAPK through the ectodomain shedding of HB-EGF in SKOV3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 55 publications
1
36
2
Order By: Relevance
“…In addition, Yagi and colleagues recently reported that a chemotherapeutic agent, paclitaxel, induced transient ERK and Akt activation through elevated expression and ectodomain shedding of HB-EGF, resulting in the escape from apoptosis. CRM197, a nontoxic mutant of diphtheria toxin and a specific inhibitor of HB-EGF, showed synergistic antitumor activities with paclitaxel by restoring the sensitivity to paclitaxel in ovarian cancer SKOV-3 cells (13). These studies suggest that an anti-HB-EGF agent is expected to be effective and exert synergistic antitumor activities with chemotherapeutic agents such as paclitaxel against ovarian cancer.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, Yagi and colleagues recently reported that a chemotherapeutic agent, paclitaxel, induced transient ERK and Akt activation through elevated expression and ectodomain shedding of HB-EGF, resulting in the escape from apoptosis. CRM197, a nontoxic mutant of diphtheria toxin and a specific inhibitor of HB-EGF, showed synergistic antitumor activities with paclitaxel by restoring the sensitivity to paclitaxel in ovarian cancer SKOV-3 cells (13). These studies suggest that an anti-HB-EGF agent is expected to be effective and exert synergistic antitumor activities with chemotherapeutic agents such as paclitaxel against ovarian cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Ovarian cancer patients with high HB-EGF expression had significantly worse prognosis than those with low HB-EGF expression (7). In addition, HB-EGF is suggested to be involved in tumor resistance against chemotherapeutic agent, paclitaxel (13). These results indicate that inhibition of HB-EGF function is a promising strategy for ovarian cancer therapy.…”
Section: Introductionmentioning
confidence: 92%
“…IL-6 and IL-8 are also important contributors to ovarian cancer angiogenesis, as demonstrated in preclinical models (34 -36). A few preclinical studies demonstrated the efficacy of different HB-EGF inhibitors in the reduction of ovarian tumor growth when administered alone or in combination with paclitaxel (37,38). Thus modulation of expression of multiple angiogenic cytokines through HB-EGF represents an attractive opportunity to target ovarian tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel has been reported to activate Akt (Mabuchi et al, 2002;Hokeness et al, 2005) and MAPK pathways (Liu et al, 2001;Kuo et al, 2006;Yagi et al, 2009) and thereby compromises its apoptotic potential, whereas inhibition of these pathways by curcumin increases susceptibility of cancer cells to chemotherapeutic agents (Bava et al, 2005;Aggarwal et al, 2006;Gagnon et al, 2008). Although activated JNK contributes to some apoptotic responses, the JNK-dependent apoptotic signaling pathways can be blocked by activation of NF-kB and Akt pathways (Xia et al, 1995).…”
Section: Discussionmentioning
confidence: 99%